Optimization potentials for wastewater treatment and energy savings in industrial zones in Vietnam: Case studies - Marina Sabelfeld; Lina Streckwall; Bui Xuan-Thanh; Sven-Uwe Geißen (Case Studies in Chemical and Environmental Engineering, 2022)
Given Vietnam's continuing strong economic growth and the associated discharge of largely untreated industrial wastewater, the country's water resources are coming under increasing stress. Therefore, companies need to comply with the wastewater discharge standards despite the constant focus on production growth. However, especially small and medium-sized companies are very reserved about optimization measures in wastewater treatment due to the expectation of high investment and increasing operating costs. However, the case studies presented here show that significant improvements in wastewater treatment performance can already be achieved by optimizing existing process technology. They aim to identify such optimization potentials in the wastewater management of two industrial zones in South Vietnam. The focus is on optimizing the biological tank aeration in a central wastewater treatment plant of an industrial zone and secondly on the reestablishment of the wastewater treatment of a food company. In the first case, the total aeration energy could be reduced by up to 68%. In the case of the resumption of regulated wastewater treatment, it could be demonstrated that the discharge limits can be safely met with the existing infrastructure.